2013
DOI: 10.1016/j.quageo.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Testing the limitations of artificial protein degradation kinetics using known-age massive Porites coral skeletons

Abstract: High-temperature isothermal heating of biominerals has commonly been used to artificially accelerate protein degradation in order to extrapolate kinetic parameters to the lower temperatures experienced in vivo and in the burial environment. It is not easy to test the accuracy of these simulations due to the difficulty of finding samples of known age held at a known temperature. We compare protein degradation in the intra-crystalline organic matrix of heated (80 °C, 110 °C, and 140 °C) massive Porites sp. coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 97 publications
(208 reference statements)
0
31
0
Order By: Relevance
“…Many attempts have been made to refine the temporal resolution and generate numerical dates from kinetic experimental data (see Clarke and Murray-Wallace (2006) for a review), but recent studies have shown that high temperature kinetic experiments may not accurately mimic low temperature protein diagenesis in some biominerals (Demarchi et al., 2012; Tomiak et al., 2012). It has even been proposed that temporal resolution at the level of isotopic substages can be achieved in the Middle Pleistocene using amino acid data (Westaway, 2009, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Many attempts have been made to refine the temporal resolution and generate numerical dates from kinetic experimental data (see Clarke and Murray-Wallace (2006) for a review), but recent studies have shown that high temperature kinetic experiments may not accurately mimic low temperature protein diagenesis in some biominerals (Demarchi et al., 2012; Tomiak et al., 2012). It has even been proposed that temporal resolution at the level of isotopic substages can be achieved in the Middle Pleistocene using amino acid data (Westaway, 2009, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A similar pattern has been observed in a range of biominerals that retain a closed system of proteins (e.g. Miller et al., 1992; Crisp et al., 2013; Tomiak et al., 2013). Due to the progressive slowing of the apparent rates of hydrolysis, a logarithmic model is not appropriate to mimic the patterns of “late” diagenesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, our study on bleached Patella and recent work carried out on the closed-system (bleached powders) proteins isolated from ostrich eggshell (Crisp et al., 2013), Porites corals (Tomiak et al., 2013) and other marine molluscs (NEaar laboratory, unpublished data) has highlighted that this divergence between low- and high-temperature data is a phenomenon that can be observed across a range of biominerals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations